Animal models of tauopathy - Westaway, David (Henry Stewart Talks, 2021)
General considerations about animal models, Genetic and idiopathic tauopathies, Transgenic mice, Principles and practice for tau animal models, Limitations of Tg mice, Alternative approaches for modeling tauopathies, Future prospects for animal models of tauopathy